The Problems of Improving the Santri’s Potential Creativity Through Arabic Literacy Skills - Badrut Tamam Efendi; Mirwan Akhmad Taufiq (Journal of Arabic Language Studies and Teaching, 2021)
Nowadays, pesantren are institutions of Islamic religious knowledge, however, students do not only learn the Qu’ran and the yellow book but they are also taught general knowledge, especially literacy. Limitations of media and internet access affect the intensity of the students writing skills so that the students' writing creativity becomes a contradiction in developing the productivity of the writing tradition in the pesantren. This research is a qualitative study using a phenomenological approach, which describes the problems and potentials of writing PP Darul Ulum Banyuanyar. Data collection was held by observation and interviews. The research findings show that the problem of students is using electronic media and internet access. However, the way students overcome limitations is by writing in diary books, Islamic boarding school mading, bulletin and magazines. The thing that supports writing creativity is the existence of a role model from the tutor and becomes a liaison for publishing works in the media.